For example, the expression $\left(\frac{x}{y}\right)^2$(xy)2 can be expanded in the following way: $\frac{x}{y}\times\frac{x}{y}=\frac{x\times x}{y\times y}$xy×xy=x×xy×y$=$=$\frac{x^2}{y^2}$x2y2. This shows that $\left(\frac{x}{y}\right)^2=\frac{x^2}{y^2}$(xy)2=x2y2

Similarly, an expression like $\left(\frac{3x}{2y}\right)^3$(3x2y)3 expands to $\frac{3x\times3x\times3x}{2y\times2y\times2y}=\frac{27x^3}{8y^3}$3x×3x×3x2y×2y×2y=27x38y3. This shows that $\left(\frac{3x}{2y}\right)^3=\frac{27x^3}{8y^3}$(3x2y)3=27x38y3.